Studi Perencanaan Embung Lapangan Jegreg Kecamatan Lengkong Kabupaten Nganjuk Provinsi Jawa Timur - Al Huda, Reja Palevi; Asmaranto, Runi; Dermawan, Very (Jurnal Teknologi dan Rekayasa Sumber Daya Air, 2021)
The problem in dry season is about water availability, while during wet season there are often several puddles in an area in Jegreg Village in Nganjuk Regency. This is due to the increasing need of the population which is not in line with the development of water supply facilities and infrastructure. In this study, the authors make an analysis related to this problem, by planning a reservoir that can be used to accommodate water during the rainy season so that can be used to reduce floods.Based on the analysis, the dead storage volume (Sediment) are 9,49 m3,  and the effective storage volume are 68,96 m3and then the total storage volume are  78,45 m3 . The height of ponds is 3 meters , with the spillway type is side channel spillway with 0,5 meter of  height. In elevation +40,50 the width of spillway are 17,15 meters. In stability analysis, the analysis used in the slope stability of the reservoir is the Bishop method with  Geostudio2012 application and from the results of the analysis, the safety number meets the requirements. For the analysis of spillway safety against shear and rolling forces, in normal, flood condition, and earthquakes condition, the safety figures meet the requirement.